2009
DOI: 10.1093/chemse/bjp089
|View full text |Cite
|
Sign up to set email alerts
|

Coactivation of Gustatory and Olfactory Signals in Flavor Perception

Abstract: It is easier to detect mixtures of gustatory and olfactory flavorants than to detect either component alone. But does the detection of mixtures exceed the level predicted by probability summation, assuming independent detection of each component? To answer this question, we measured simple response times (RTs) to detect brief pulses of one of 3 flavorants (sucrose [gustatory], citral [olfactory], sucrose-citral mixture) or water, presented into the mouth by a computer-operated, automated flow system. Subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 38 publications
3
61
1
Order By: Relevance
“…It has been shown that the coactivation of taste and odour signals is rapid, suggesting that olfactory and gustatory flavour signals integrate automatically, relatively early in flavour processing, especially before the ontogenesis of attentional or decisional processes (Veldhuizen, Shepard, Wang, & Marks, 2010). Nevertheless, several studies reported an impact of attentional processes on odour-taste integration (Clark & Lawless, 1994;Frank, van der Klaauw, & Schifferstein, 1993;Marks et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the coactivation of taste and odour signals is rapid, suggesting that olfactory and gustatory flavour signals integrate automatically, relatively early in flavour processing, especially before the ontogenesis of attentional or decisional processes (Veldhuizen, Shepard, Wang, & Marks, 2010). Nevertheless, several studies reported an impact of attentional processes on odour-taste integration (Clark & Lawless, 1994;Frank, van der Klaauw, & Schifferstein, 1993;Marks et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Receptors relay sensory signals to the brain, which segregates, evaluates, and distinguishes the stimuli, leading to the experience known as "flavor." [1][2][3] The complexity of gustatory processing is now appreciated and has become an area of much interest and research. The processing of taste information is essential for mediating food preference and, as a result, weight maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of redundancy gain experiments have focused on and demonstrated the effect in cognitively low level tasks such as target detection [16], [17], [18]. There have however been some redundancy gain experiments that utilized cognitively high level processing which include fame decision judgment for faces [9], [19], [10] emotion recognition tasks [20], [21], [22], [23] and lexical decision tasks [24], [7], [25], [8].…”
Section: A Introductionmentioning
confidence: 99%